2009
DOI: 10.1364/josaa.26.002033
|View full text |Cite
|
Sign up to set email alerts
|

Statistical investigation of the double random phase encoding technique

Abstract: The amplitude-encoding case of the double random phase encoding technique is examined by defining a cost function as a metric to compare an attempted decryption against the corresponding original input image. For the case when a cipher-text pair has been obtained and the correct decryption key is unknown, an iterative attack technique can be employed to ascertain the key. During such an attack the noise in the output field for an attempted decryption can be used as a measure of a possible decryption key's corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…There has been significant interest in encryption schemes which can be implemented optically [18][19][20][21][22][23]. Practical optical implementation of such systems is difficult [19,22] and the security and robustness of these systems is still a matter of study and analysis [18,[20][21][22][23].…”
Section: Optical Encryptionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been significant interest in encryption schemes which can be implemented optically [18][19][20][21][22][23]. Practical optical implementation of such systems is difficult [19,22] and the security and robustness of these systems is still a matter of study and analysis [18,[20][21][22][23].…”
Section: Optical Encryptionmentioning
confidence: 99%
“…Practical optical implementation of such systems is difficult [19,22] and the security and robustness of these systems is still a matter of study and analysis [18,[20][21][22][23]. However not only do such systems pose a very interesting problem for the fast algorithms described above in Section 3, it has been shown that the problems of encryption and multiplexing can be discussed fruitfully using PSO [24].…”
Section: Optical Encryptionmentioning
confidence: 99%
“…Furthermore, two dimensional optical encryption processing has been extended into a three dimensional spacebased encryption processing, where each pixel of the image is axially considered as one particle and phase-shifting digital holography technique is applied to the diffraction of all pixels in space (particles) [71][72][73][74]. In the context of cryptography and cryptoanalysis, both chosen-plaintext [60] and known-plaintext attack [75][76][77] on DRPE have been examined, as have several other attacking methods [78][79][80][81][82] and the key space of DRPE technique itself [83][84][85][86] has also been analysed.…”
Section: Introductionmentioning
confidence: 99%
“…The original image can be extracted only when appropriate keys are given. Even though the DRPE algorithm has performed well in the image security field [6,7], it has been reported that DRPE is vulnerable to chosen-cipher text attacks [8,9]. Therefore, the encryption keys used in DRPE could be reproduced by an intruder who has repeatedly accessed the DRPE system.…”
Section: Introductionmentioning
confidence: 99%